ANALISIS PENGARUH KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DAN LOYALITAS PELANGGAN (Studi Kasus Pada Bengkel AHASS Area Purwokerto ) - Andang Nofiana; Hengky Widhiandono (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2017)
This research has aim to partially analyse the effects: 1) Work satisfaction on worker’s performance, 2) work satisfaction on customer loyalty, 3) worker’s performance on customer loyalty. The type of research is a survey research.The research was conducted in AHASS (Astra Honda Authorized Service Station) service station Purwokerto division which amounted to 9 locations, the research used 101 tecnician or mechanic and customer service as wellas 101 service customers as respondents. The hypothesis verification used linier regression analysis. The result was: 1) Work satisfaction has positive significant effect on worker’s performance, 2)Work satisfaction has no significant effect on customer’s loyalty, 3) Worker’s performance has effect on customer’s loyalty.Keywords: Work satisfaction, Worker’s performance, Customer’s loyalty